Democratization of ecosystem services—a radical approach for assessing nature's benefits in the face of urbanization. Issue 5 (4th May 2018) - McHale, Melissa R.; Beck, Scott M.; Pickett, Steward T. A.; Childers, Daniel L.; Cadenasso, Mary L.; Rivers, Louie; Swemmer, Louise; Ebersohn, Liesel; Twine, Wayne; Bunn, David N
ABSTRACT: Objectives: (1) To evaluate how ecosystem services may be utilized to either reinforce or fracture the planning and development practices that emerged from segregation and economic exclusion; (2) To survey the current state of ecosystem service assessments and synthesize a growing number of recommendations from the literature for renovating ecosystem service analyses. Methods: Utilizing current maps of ecosystem service distribution in Bushbuckridge Local Municipality, South Africa, we considered how a democratized process of assessing ecosystem services will produce a more nuanced representation of diverse values in society and capture heterogeneity in ecosystem structure and function. Results: We propose interventions for assessing ecosystem services that are inclusive of a broad range of stakeholders' values and result in actual quantification of social and ecological processes. We demonstrate how to operationalize a pluralistic framework for ecosystem service assessments. Conclusion: A democratized approach to ecosystem service assessments is a reimagined path to rescuing a poorly implemented concept and designing and managing future social-ecological systems that benefit people and support ecosystem integrity.  It is the responsibility of scientists who do ecosystem services research to embrace more complex, pluralistic frameworks so that sound and inclusive scientific information is utilized in decision-making.